Improving Students' Speaking Skill Using Hello English Application as a Medium of Learning from Home - Nurul Aini; Firdausi Amalia; Ary Setya Budhi Ningrum (Institut Agama Islam Negeri Palopo, 2022)
This study aims to improve stduents’ speaking skill using hello English application. The subjects of this study were the fifth-grade students of SDN Sidorejo 1 Mojokerto. The researcher used classroom action research to conduct this study. The research instruments were an observation sheet, questionnaire sheet, test, and documentation. This study was done in two cycles. The researcher procedures of this research consisted of four steps. They are planning, implementing, observing, and reflecting. The criteria of success were 75% of students got a score of 9.From the findings and discussion, the result is Hello English application can improve students’ speaking skills. It can be seen in the test of cycle 2. In cycle 2, the result of students’ speaking scores showed that 15 students passed and 2 of the students were failed. The mean scores of the test in cycle 2 were 9,05 and the percentage of improvement 88,23%. It is showed that in cycle 2, the students' scores passed the criterion of success 75%. Thus, based on the result of cycle 2 Hello English application can improve students’ speaking skills.